Parasites’ species diversity analysis of separate fish species in freshwater reservoirs of Ukraine. Monogenetic flukes - Melnychuk, V.; Yevstafieva, V.; Prima, O.; Shepitko, A.; Myroshnychenko, A.; Chaus, Ya.; Turchenko, Ya. (Scientific Progress & Innovations, 2022)
Ukraine has extremely large water spaces, which include reservoirs, ponds, lakes, large and small rivers, irrigation ditches, and other water resources. Currently, within each territorial community of the region, it is possible to count up to several dozen economic entities of various forms of ownership that in one way or another connect their activities with fishing. That is why problems related to fish diseases in aquaculture are now quite relevant. Fish diseases of parasitic etiology occur both in natural and human made reservoirs, causing significant damage to fish farming. The study of diseases caused by monogenetic flukes and monogenean fish fauna in freshwater reservoirs not only expands knowledge about the biodiversity of hydrofauna, but is also of great importance when carrying out acclimatization works, introducing new breeding facilities in aquaculture, and predicting the occurrence of epizootics. Therefore, the purpose of the review was to determine the state of monogenean fauna of individual fish species in freshwater reservoirs of Ukraine. In the work, nine species of fish (grass carp, silver carp, sand grubby, perch, crucian carp, pike, rudd, carp, and roach), that are part of the core of the ichthyocenosis of the majority of water bodies of Ukraine were selected as the object of the review. It was found out that the monogenean fish fauna includes 33 species, which according to their systematic position belong to 4 families – Gyrodactylidae Cobbold, 1864, Dactylogyridae Bychowsky, 1933, Diplozoidae Palombi, 1949 and Tetraonchidae Monticelli, 1903 of the Monogenea class. According to scientists, the fauna of monogenetic flukes in crucian carp was the richest, which included 18 types of parasites. In the fauna of grass carp and roach, 8 and 7 species of monogenetic sisuses were counted, respectively. The identified causative agents of monogenean crucian carp, grass carp and roach belong to the 3 families Gyrodactylidae, Dactylogyridae and Diplozoidae according to their systematic position. The researchers found 6, 5, and 2 species of monogeneans, respectively, belonging to the families Gyrodactylidae and Dactylogyridae in the silver carp, carp, and roach. The monogenean fauna of pike, perch, and sand grubby turned out to be poor, scientists found one type of parasite each in these fish species. In particular, in the pike – Tetraonchus monenteron Dsesing, 1858, in the perch Dactylogyrus sphyrna Linstow, 1878, in the sand grubby Gyrodactylus proterorhini Ergens, 1967. Among the discovered monogeneans, the species G. elegans von Nordmann, 1832, D. extensus Mueller & Van Cleave, 1932 and D. vastator Nybelin, 1924 were the least species-specific regarding the choice of the definitive host, they were detected on 6, 5, and 4 fish species, respectively.